Comorbidity results of an obesity center - Tuna, Müjgan; Kırlak, Şenay; Akın, Seydahmet; Çakır Madenci, Özlem (The European Research Journal, 2025)
Objectives: Obesity is linked to numerous severe health conditions, including type 2 diabetes mellitus, heart disease, hypertension, and stroke. This study aimed to compare metabolic parameters and anthropometric measurements between male and female patients with obesity to identify gender-based differences in obesity-related health markers. Methods: This prospective study enrolled 393 obese patients (52 male, 341 female) from an outpatient clinic. After an overnight fast (8-10 hours), blood samples were collected to assess a range of parameters: complete blood count, fasting blood glucose, insulin, Hemoglobin A1c (HbA1c), Aspartate aminotransferase (AST), Alanine aminotransferase (ALT), Thyroid-stimulating hormone (TSH), total cholesterol, triglycerides, Low-density lipoprotein (LDL), High-density lipoprotein (HDL), 25-hydroxy vitamin D3 (25OHD3), ferritin, iron, and vitamin B12. Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) and Body Mass Index (BMI) were calculated, while soft lean mass (SLM) and percent body fat (PBF) were also analyzed. Results: Males with obesity had significantly higher levels of insulin, HOMA-IR, 25OHD3, ferritin, iron, hemoglobin, hematocrit, urea, and ALT compared to females (P<0.05 for all). Conversely, males had lower HDL and platelet levels (P<0.05). The prevalence of thyroid disease was significantly higher in females (P=0.027). Conclusions: Thyroid disease prevalence was significantly higher in females compared to males. Additionally, metabolic parameters such as insulin, HOMA-IR, and urea were elevated in females, while HDL and platelet levels were lower in males.